Unconventional monetary policy: between the past and future of monetary economics - Mattia Guerini; Francesco Lamperti; Andrea Mazzocchetti (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
In this paper we discuss some of the monetary policy issues that have involved major central banks worldwide since the 2008 financial crisis, and which remain open. We provide an excursus of the unconventional monetary policies adopted by central banks in the last decade, focusing on the European Central Bank and the Federal Reserve, and we discuss the rationale and efficacy of some unconventional monetary instruments, of inflation targeting and of central-bank independence. We also provide a perspective on possible future developments of monetary policy. We argue that while unconventional monetary policy was useful, there is still ample space for improvement: in the recessions to come, unconventional monetary policy will need to be better coordinated with fiscal, micro- and macro-prudential policies to provide more inclusive results that might positively affect the real economy beyond the financial system.
Keywords: E51; E52; E58; E61; 330; unconventional monetary policies; inflation targeting; central-bank independence